Perancangan aplikasi e-persuratan berbasis web menggunakan framework codeigniter pada direktorat lalu lintas dan angkutan laut kementerian perhubungan - Gina Mulyani; Zulhalim Zulhalim; Verdi Yasin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
Designing a Web-based e-correspondence application using the CodeIgniter framework at the Directorate of Traffic and Sea Transportation is very much needed because the administrative process for managing correspondence is still using office applications. Moreover, since the Covid-19 pandemic occurred, which resulted in the division of the implementation of official duties at the office (WFO) and official duties at home (WFH), which required the letter disposition process that was previously carried out through the WhatsApp group to be less effective and efficient. Moreover, a large number of lost letter files and limited access resulted in the process of posting letters being hampered, which affected the performance of the Directorate of Traffic and Sea Transportation. By conducting and descriptive qualitative research, namely research that takes existing problems by describing the object that is the subject of the problem by collecting, compiling, analyzing, interpreting it in the form of a report. Data collection techniques using interview techniques, data observation, document analysis, and concluding. It is hoped that this application can simplify the process of recording, disposing of, numbering, and storing letters at the Directorate of Traffic and Sea Transportation.